Efecto y evaluación agrícola de digestato anaeróbico de la FORSU como fertilizante en tritical invernal - Salcedo-Serrano, Daniel Alejandro; Cano-Ríos , Pedro; Gutiérrez-Castillo, María Eugenia; Álvarez-Reyna, Vicente de Paul; Gállego-Bravo, Aixa Kari; Tovar-Gálvez, Luis Raúl (Ecosistemas y Recursos Agropecuarios, 2022)
Anaerobic Digestion (AD) has proven to be an economically viable technology to treat the organic fraction of the municipal solid wastes (OFMSW). Research regarding the management and application of AD byproducts in Mexico, is required to encourage the private sector and local administrations to invest in this technology. In this study, fodder winter triticale (x triticosecale Wittm. ex A. Camus var. Rio Nazas) was grown to demonstrate the fertilizer effect and to evaluate the raw digestate generated from the AD under thermophilic conditions of locally sampled OFMSW, using a batch scale digester. The digestate produced was incorporated into a 6 m2 plot according to the recommender fertilization for this crop. At the same time, a crop treated with inorganic fertilizer (IF) and a control were grown, each on a plot of same dimensions, for comparison purposes. The fertilizer effect was measured in crop yield (Mg ha−1), seed efficiency (kgTriticale kgSeed−1) and bromatological value. Overall, the digestate treatment had better results in crop yield (12.54 Mg ha−1) and seed efficiency (83.61 kgTriticale kgSeed−1) than those achieved with the IF (11.16 Mg ha−1 and 74.43 kgTriticale kgSeed−1 , respectively) and the control. Whereas the bromatological value, a statistical analysis revealed that, regardless of the treatment, the mineral uptake, protein, sugar and fiber content were not significantly different (p > 0.05). Raw digestate generated from AD of the OFMSW under thermophilic conditions, is a valuable by product, rich enough to fully substitute IF for growing triticale Río Nazas.